2015
DOI: 10.1002/nau.22906
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors to develop autonomic dysreflexia during urodynamic examinations in patients with spinal cord injury

Abstract: According to our results, the patient's age and maximum detrusor voiding pressure should be considered at the time of performing a UD examination in order to prevent the sudden onset of AD in patients with SCI above Th6. Neurourol. Urodynam. 36:171-175, 2017. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Linsenmeyer et al 12 found urodynamic examination to be an excellent way to detect whether individuals with SCI are prone to asymptomatic AD. Previous studies revealed incidences of AD during urodynamics, [11][12][13][14][15][16] but the diagnostic criteria varied among these studies. Some studies 12,13 used maximal SBP and DBP as criteria, whereas others 11,[14][15][16] just used SBP change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Linsenmeyer et al 12 found urodynamic examination to be an excellent way to detect whether individuals with SCI are prone to asymptomatic AD. Previous studies revealed incidences of AD during urodynamics, [11][12][13][14][15][16] but the diagnostic criteria varied among these studies. Some studies 12,13 used maximal SBP and DBP as criteria, whereas others 11,[14][15][16] just used SBP change.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed incidences of AD during urodynamics, [11][12][13][14][15][16] but the diagnostic criteria varied among these studies. Some studies 12,13 used maximal SBP and DBP as criteria, whereas others 11,[14][15][16] just used SBP change. The International Standards to document remaining Autonomic Function after Spinal Cord Injury (ISAFSCI) 17 recommends the diagnostic criteria for AD as a SBP increase of 420 mm Hg from baseline.…”
Section: Introductionmentioning
confidence: 99%
“…This was done specifically in support of the findings of a 2017 study, showing that a patients age (>45 years), completeness of injury, and the symptoms of chills or sweating, are risk factors for AD symptoms occurring during UDS. 28 In our study all participants had a complete SCI (i.e., AIS A or B), half the cohort was over 45 years of age, and 30% presented with sweating during UDS. Risk factor prediction of AD symptoms is a potentially useful tool in the clinical setting especially as patients are able to state their symptoms throughout a procedure.…”
Section: Discussionmentioning
confidence: 86%
“…B. bei der urodynamischen Untersuchung Querschnittgelähmter unbedingt zu beachten. Diese Komplikation wird bei mehr als 50% der betroffenen Patienten beobachtet [43].…”
Section: Besonderheiten Bei Diagnostischen Eingriffenunclassified